2019
DOI: 10.1016/j.parkreldis.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Orally inhaled levodopa (CVT-301) for early morning OFF periods in Parkinson's disease

Abstract: Background: CVT-301 (Inbrija) is a self-administered orally inhaled levodopa approved for the intermittent treatment of OFF episodes in patients with Parkinson's disease (PD) treated with carbidopa/levodopa. Prior studies only evaluated CVT-301 after the first ON of the day. Objective and methods: The objective of this study was to evaluate the safety and tolerability of CVT-301 for early morning OFF. Using a randomized, double-blind, 2-way crossover design, eligible patients in the morning OFF state (having n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…On clinic pulmonary evaluations, most patients had <10% change from pre-dose values and tolerated exposure well. TEAEs were generally consistent with those for oral LD except for cough, an expected side-effect with dry powder inhalation, previously reported with CVT-301 [6,10]. Most cough AEs were mild, and all resolved by end of study (although one patient was lost to follow-up).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…On clinic pulmonary evaluations, most patients had <10% change from pre-dose values and tolerated exposure well. TEAEs were generally consistent with those for oral LD except for cough, an expected side-effect with dry powder inhalation, previously reported with CVT-301 [6,10]. Most cough AEs were mild, and all resolved by end of study (although one patient was lost to follow-up).…”
Section: Discussionsupporting
confidence: 79%
“…Patients were instructed to avoid using CVT-301 for their early morning OFF period prior to their oral CD/LD dose because CD levels in the morning would be low. This was investigated in another study [10] which assessed the safety of CVT-301 when given for morning OFF, after which patients were permitted to take it for early morning OFF. Therefore, for much of the time, the mean number of daily OFF periods that patients were allowed to treat with CVT-301 in the study (which excluded morning OFF) was approximately 2.5 OFF periods daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study randomizing patients to either a single dose of 84 mg inhaled levodopa or placebo immediately following their first morning dose of oral carbidopa/ levodopa, there were no apparent increases in treatmentrelated adverse events including symptomatic orthostatic hypotension, nausea, or dyskinesia. An exploratory efficacy assessment found that median time-to-ON was 25.0 min following oral CD-LD IR+ inhaled levodopa versus 35.5 min following oral CD-LD IR+ inhaled placebo [66].…”
Section: Orally Inhaled Levodopamentioning
confidence: 99%
“…ND062L is a transcutaneous formulation of l -dopa/carbidopa in a patch-pump device [177]. CVT-301 is a l -dopa inhalation, used as a “rescue” therapy for sudden off: a single dose of 84 mg, administered in association with oral l -dopa/carbidopa, for early morning off symptoms seems to be well-tolerated and effective [178,179]. A randomized controlled trial (RCT) has shown that Levodopa-carbidopa intestinal gel (LCIG), administered by continuous intra-intestinal infusion (Duodopa ® ), was more effective than oral l -dopa regarding motor fluctuations.…”
Section: Complicated Stage: Pharmacological Treatment For Motor Comentioning
confidence: 99%